(untitled) (Journal of Computational Mathematics, 1986)
In this paper, we give a recursive algorithm for computing the weighted Moore-Penrose inverse A^+_MN. This method is a generalization of Greville's method for computing Moore-Penrose inverse A^+, and the technique of its proof is new. This method suits the weighted least-squares problem.